2002
DOI: 10.1110/ps.0213702
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐enhanced enzyme reaction for protein mapping by mass spectrometry: A new approach to protein digestion in minutes

Abstract: Accelerated proteolytic cleavage of proteins under controlled microwave irradiation has been achieved. Selective peptide fragmentation by endoproteases trypsin or lysine C led to smaller peptides that were analyzed by matrix-assisted laser desorption ionization (MALDI) or liquid chromatography-electrospray ionization (LC-ESI) techniques. The efficacy of this technique for protein mapping was demonstrated by the mass spectral analyses of the peptide fragmentation of several biologically active proteins, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
145
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(149 citation statements)
references
References 41 publications
3
145
1
Order By: Relevance
“…The mass difference between the measured molecular weights of the two isoforms is 1380 Da, which is close to the 1413 Da proposed by the translated protein sequences based on the two cDNAs. Previous characterization of Ara h 2 provided the identification of an N-terminal peptide [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and two tryptic peptides [82][83][84][85][86][87][88][89][90][91][92][93][94] and [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110], which were proposed as potential biomarkers for regulatory monitoring. 6 A recent study of 2-D gel electrophoretic patterns of proteins from the Virginia type peanut identified fourteen spots that were linked to Ara h 2 by partial peptide mass fingerprinting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass difference between the measured molecular weights of the two isoforms is 1380 Da, which is close to the 1413 Da proposed by the translated protein sequences based on the two cDNAs. Previous characterization of Ara h 2 provided the identification of an N-terminal peptide [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and two tryptic peptides [82][83][84][85][86][87][88][89][90][91][92][93][94] and [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110], which were proposed as potential biomarkers for regulatory monitoring. 6 A recent study of 2-D gel electrophoretic patterns of proteins from the Virginia type peanut identified fourteen spots that were linked to Ara h 2 by partial peptide mass fingerprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave acceleration was used to enhance the enzymatic (trypsin) proteolysis of the reduced isoforms. 9 Then the peptide products were analyzed using LC-MS/MS. Manual interpretation of the MS/MS spectra allowed de novo sequencing of the primary structures of all the isoforms of the Ara h 2 and identification and location of the PTM.…”
Section: Introductionmentioning
confidence: 99%
“…This approach exploits unique microwave properties to accelerate the enzymatic digestion. In recent years, microwaveassisted proteolytic digestion procedures, including tryptic [6][7][8] and acid-mediated proteolysis [9][10][11][12], have enabled samples to be prepared more rapidly for bottom-up analysis.…”
mentioning
confidence: 99%
“…For example, microwave-assisted [6] digestion, proposed by Pramanik et al in 2002 [7], successfully reduced the digestion time from hours to 10 min. Turapov et al reported a fast digestion method using a PCR-type thermocycler [8], with the caveat that many proteases cannot withstand the elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%